The influence on women's sexual functions of education given according to the PLISSIT model after hysterectomy - YILDIZ, HATİCE (ELSEVIER SCIENCE BV, 2012)
Aim: The purpose of this study was to detennine the influence on the sexuality of Ivomen of education is given to women according to the PLISSIT model after the total abdominal hysterectomy and bilateral salpingo-oophorectomy (TAH+BSO) surgery. Metod: The study was planned and carried out as a prospective, randomize controlled study. The sample of the study was formed on the total 70 women who had been operated TAH+BSO. The participated women were randomized as a working group (n=35) and control group (n=35). Data were collected with the questionnaire form, Female Sexual Function Index (FSFI) and the evaluation tbnn of the PT ISSIT model education program. The FSFI was applied tbur times to the women (two times before surgery and two times in the 3rd and 6th months after surgery). The PLISSIT model education program was applied only for working group.Results: Analysation of results has showed the participant women's sexual function in both groups are same before not occured the indications for the hysterectomy operation. But in the semptomatic period, it was determined that women's sexual functions were negatively affected in both groups. The postoperative 3rd and 6th months' results were showed sexual functions of women who had given education according to the PLISSIT model had better than the control group. And the control group experienced higher rates of sexual dysfunction. In addition the Ivomen in the working group were more successful in dealing with sexual problems after surgery. As a conclusion, the education of svomen according to the PLISSIT model after hysterectomy had positive effect on sexual functions and problem solving skills about sexuality (C) 2012 Published by Elsevier Ltd. Selection
Keywords: Education; PLISSIT model; sexual function; hysterectomy; ABDOMINAL HYSTERECTOMY